2022
DOI: 10.1186/s41256-022-00261-3
|View full text |Cite
|
Sign up to set email alerts
|

Examining enablers of vaccine hesitancy toward routine childhood and adolescent vaccination in Malawi

Abstract: Background The contribution of vaccination to global public health and community wellbeing has been described as one of the greatest success stories of modern medicine. However, 13.5 million children still miss at least one of their routine vaccinations, and this contributes to about 1.5 million deaths from vaccine-preventable diseases. One of the contributing factors has been associated with vaccine hesitancy. Vaccine hesitancy is the delay or refusal of vaccines despite their availability. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 24 publications
0
24
0
2
Order By: Relevance
“…Since mothers/caregivers from these religions are likely not be found at under 5 clinic to learn the importance of malaria vaccines, even if they are willing to be vaccinated their religous leader will prevent them from accessing the health services. This was also evidenced in a study conducted by Adeyanju et al, 2022 in Malawi, which reported that religious groupings, for example Zion and Apostolic faith, were prohibiting their members from visiting the hospital and accessing vaccines [19].…”
Section: Discussionmentioning
confidence: 80%
“…Since mothers/caregivers from these religions are likely not be found at under 5 clinic to learn the importance of malaria vaccines, even if they are willing to be vaccinated their religous leader will prevent them from accessing the health services. This was also evidenced in a study conducted by Adeyanju et al, 2022 in Malawi, which reported that religious groupings, for example Zion and Apostolic faith, were prohibiting their members from visiting the hospital and accessing vaccines [19].…”
Section: Discussionmentioning
confidence: 80%
“…These situations are complicated during armed conflicts where husbands are deployed to defend the community or prosecute a war. Masculinity, as a significant determinant of healthcare-seeking behavior in SSA and an emerging area of global health research, have been strongly linked to child health outcomes [70][71][72]. However, this review shows that its effects extend beyond child health to include maternal health and possibly other health-seeking behavior within households in SSA.…”
Section: Factors Influencing Health-seeking Behavior In Armed Conflic...mentioning
confidence: 86%
“…Caregivers therefore face a dilemma about whether to protect their daughter’s reproductive future with a vaccine that might compromise this very capacity. This fear that the HPV vaccine could affect fertility has been noted in LMIC settings [14] , [15] , [16] , [17] , [18] , [19] , [20] ; and there are many similar rumors in Malawi and throughout Africa about infertility related to vaccines and other public health interventions [21] , [22] . Research should further interrogate these perceptions—including survey questions about this belief rather than generic “side effects,” as it appears to be a specific and salient concern; and the public health community should work to develop effective approaches to reassuring caregivers in Malawi about the safety of the vaccine and lack of evidence showing fertility-related impacts.…”
Section: Discussionmentioning
confidence: 99%